Rancang Bangun Aplikasi Penjadwalan Akademik Menggunakan Algoritma Tabu Search di Surabaya Hotel School - Muhammad Hoiril Miftah; Bambang Hariadi; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The purpose of this thesis is to produce a combination of optimal schedule where no severe conflicts and conflicts minimal value by searching the tabu search method and take into account a number of variables such as instructor schedule, the number of students, lectures limited time and space. So that the resulting schedule can help organize the lecture. With the scheduling of lectures using tabu search algorithm can help in pebuatan class schedules, especially in terms of making the course schedule with a minimum value of conflict or absence komflik courses, lecturers and rooms at a time.